Das Bekenntnis von Ex 14,31 - Herrmann, Wolfram (Biblische Notizen, 2007)
Ex 14:31 transgresses by the deduction contained in it the border of the preceding legend. Because moreover 15:1 joins 14:30 without gap one should see in verse 31 a faithful manifestation speaking of belief in Yahweh and in Moses.